Fuel rod design for a high burnup small modular nuclear reactor - Octadamailah, S.; Sigit, R.; Ismarwanti, S.; Suryaman, G. K.; Ghufron, H.; Dewayatna, W.; Himawan, R.; Dewita, E.; Bakhri, S.; Purwadi, M. D. (Journal of applied research and technology, 2025)
PWR is a type of nuclear reactor that is widely used as a nuclear power plant. Even though PWR has been around for a long time,  technology continues to develop. The direction of development of PWR technology is to create a more compact design with a modular system (SMR) and more efficient fuel. More efficient fuel can be obtained by increasing fuel burnup. By increasing burnup, the fuel usage period is longer, thereby increasing the economic value of the fuel and reducing the volume of radioactive waste produced from spent fuel. High burnup means the fuel will be exposed to radiation for longer. Therefore, it is necessary to calculate both thermal and mechanical aspects with the new fuel rod design, to see whether the fuel can be used until the end of the fuel cycle. Calculations wereconducted using the Femaxi version 6 code. From the calculation results, it was obtained that the dimensions of the fuel rods were capable of reaching a burnup of 60 GWd/TU. The dimensions obtained include the diameter and length of the pellets of 7.4 mm and 10 mm, the diameter and depth of the disc of 4.7 mm and 0.51 mm, and the inner and outer diameters of the cladding of 7.8 mm and 9.3 mm. The calculation results show that the temperature distribution in the fuel rods during reactor operation is still within safe limits, and pellet cladding interaction (PCI) does not occur until the end of the fuel consumption cycle.